2015
DOI: 10.1186/s40623-015-0345-5
|View full text |Cite
|
Sign up to set email alerts
|

Total (fumarolic + diffuse soil) CO2 output from Furnas volcano

Abstract: Furnas volcano, in São Miguel island (Azores), being the surface expression of rising hydrothermal steam, is the site of intense carbon dioxide (CO2) release by diffuse degassing and fumaroles. While the diffusive CO2 output has long (since the early 1990s) been characterized by soil CO2 surveys, no information is presently available on the fumarolic CO2 output. Here, we performed (in August 2014) a study in which soil CO2 degassing survey was combined for the first time with the measurement of the fumarolic C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…This is for instance the case at Furnas, where 60-90 per cent of dwellings are built over hydrothermal CO 2 emission zones (Viveiros et al 2010). In addition, hydrothermal explosions were reported in one of the fumaroles located close to Furnas village (Pedone et al 2015, and references therein). Along The Azores islands are located at the triple junction between the North American, Eurasian and African plates.…”
Section: Introductionmentioning
confidence: 92%
“…This is for instance the case at Furnas, where 60-90 per cent of dwellings are built over hydrothermal CO 2 emission zones (Viveiros et al 2010). In addition, hydrothermal explosions were reported in one of the fumaroles located close to Furnas village (Pedone et al 2015, and references therein). Along The Azores islands are located at the triple junction between the North American, Eurasian and African plates.…”
Section: Introductionmentioning
confidence: 92%
“…Techniques to quantify CO 2 remotely and from smaller features have also developed in recent years. Tunable diode laser spectrometer [60][61][62] measurements have shown that the CO 2 output from fumaroles is significant (hundreds of t/d) at some volcanoes, illustrating a nontrivial contribution to the volcanic CO 2 flux from this largely unquantified source at a global scale. In addition, LIDAR, specifically differential absorption LIDAR, 38,63 the smaller CO 2 differential absorption LIDAR, 39 and miniaturized light laser sensing spectrometers, 64 have been used to determine path-integrated CO 2 concentrations over kilometer scales.…”
Section: Significant Recent Advances: Continuous and Remote Techniquesmentioning
confidence: 99%
“…The Multi-GAS sensors were calibrated before the field surveys in the laboratory by using standard gas cylinders (all in nitrogen matrixes) at different concentrations within the sensor ranges. Laboratory tests indicated a typical measurement error in the CO 2 /H 2 S ratios ≤20% [67]. The Multi-GAS instrumentation was equipped with a GPS to have continuous time and space coordinates during acquisition.…”
Section: Air Concentration Of Co 2 and H 2 Smentioning
confidence: 99%